2007
DOI: 10.1097/01.inf.0000253251.03785.9b
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Immune Responses in Children Given Annual Immunization With Trivalent Inactivated Influenza Vaccine

Abstract: These findings suggest that children may plateau in CD4+ T-cell responses to influenza antigens with repeated exposures and that the number of exposures may play a large role in building a memory CD4+ T-cell response to influenza A, perhaps independently from age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…A generalized decrease of CMI or of influenza-specific CMI has not been reported by other investigators who assessed T cell responses to influenza vaccines administered to healthy individuals. 15,18,26,27 The administration of a virosomal influenza vaccine to HIV-infected children on HAART also did not appear to decrease their CMI. 28,29 ELI-SPOT assays are not standardized and there is variability across laboratories, 30,31 which may explain the difference between our results and those of others.…”
Section: Discussionmentioning
confidence: 99%
“…A generalized decrease of CMI or of influenza-specific CMI has not been reported by other investigators who assessed T cell responses to influenza vaccines administered to healthy individuals. 15,18,26,27 The administration of a virosomal influenza vaccine to HIV-infected children on HAART also did not appear to decrease their CMI. 28,29 ELI-SPOT assays are not standardized and there is variability across laboratories, 30,31 which may explain the difference between our results and those of others.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccine-induced T-cell responses have been studied in children [9,30,31], but a systemic view of age-associated influenza virus-specific CMI spanning young and adolescent children has been lacking. Our study showed that, although the overall induction of influenza virus-specific CD4 + T cells T-cell responses have been shown to be correlated with Ab responses [20], our current findings suggest that influenza virusspecific CD4 + T-cell responses may change from T H2 -prone to T H1 -prone CD4 + T-cell responses during the transition from childhood to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily on the basis of findings in animal models, T cell responses are also thought to play an important role in clearing influenza virus infection [15][16][17][18][19][20][21]. However, few studies of cellular immunity against influenza have been done in humans, especially in children given LAIV [22][23][24].…”
mentioning
confidence: 99%